The institutional organization of national gymnastics federations and the offer of coach education programs for gymnastics for all: an international analysis - Bento-Soares, D.; Marconi Schiavon, L. (Science of Gymnastics Journal, 2023)
Coach education programs by National Gymnastics Federations (NGF) can provide in-depth and specific discussions and contribute to the development of gymnastics in different countries, as they address the specific interests and the people involved with it. For these actions to take place, a certain level of organization of the institutions is required and the existence of specific committees or commissions can contribute to this process since they possess the knowledge of the area and are familiar with organization of relevant actions. This study aims to explore the provisionof coach education programs for Gymnastics for All (GFA) and the organization of NGF worldwide. In total, 44 NGFs were consulted about the existence of such committees or commissions and the promotion of coach education programs for GFA and other gymnastics modalities. We used an online questionnaire hosted on the Google Forms® platform, in four languages. The answers were processed by simple statistics and analyzed according to the research context. The responses obtained show that 36 NGFs have Technical and GFA Committees in their organization, while eight do not have such bodies (smaller institutions and still poorly structured). 30 NGFs claimed to have GFA Committees, a meaningful number. Additionally, 30 NGFs conduct coach education programs for GFA. The analysis of the data showed that there is a correspondence between the existence of Technical Committees and GFA Committees and organisation and promotion of coach education programs.